EXPLORING THE INTERSECTION OF CORPORATE GOVERNANCE AND SUSTAINABLE DEVELOPMENT GOALS: A SYSTEMATIC LITERATURE REVIEW (AUN INTERNATIONAL CONFERENCE, 2025)
Achieving the United Nations Sustainable Development Goals (SDGs) requires rethinking corporate governance to balance economic, social, and environmental objectives. This paper systematically reviews 85 peer-reviewed studies published between 2015 and 2025 to examine the intersection between corporate governance mechanisms and SDG achievement. Using a structured approach, the review identifies key governance factors, such as board composition, stakeholder orientation, transparency, and accountability, that influence firms’ contributions to sustainability outcomes. Findings reveal that while good governance enhances SDG performance through improved disclosure, ethical leadership, and stakeholder engagement, misaligned governance practices and short-term profit orientation hinder sustainable value creation. The paper highlights significant gaps in empirical evidence, particularly regarding sectoral differences, developing economies, and measurable SDG impacts. It contributes to the literature by mapping the evolving nexus between governance and sustainability, providing a foundation for future research, and offering actionable insights for policymakers and corporate leaders to strengthen governance systems for SDG alignment